2016
DOI: 10.1111/mmi.13588
|View full text |Cite
|
Sign up to set email alerts
|

cAMP‐independent signal pathways stimulate hyphal morphogenesis in Candida albicans

Abstract: Summary The fungal pathogen Candida albicans can transition from budding to hyphal growth, which promotes biofilm formation and invasive growth into tissues. Stimulation of adenylyl cyclase to form cAMP induces hyphal morphogenesis. The failure of cells lacking adenylyl cyclase (cyr1Δ) to form hyphae has suggested that cAMP signaling is essential for hyphal growth. However, cyr1Δ mutants also grow slowly and have defects in morphogenesis, making it unclear whether hyphal inducers must stimulate cAMP, or if nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 58 publications
(100 reference statements)
3
47
0
Order By: Relevance
“…E). Therefore, disruption of cAMP‐PKA signaling did not affect NRG1 transcriptional down‐regulation and GlcNAc‐induced filamentation, a finding which is consistent with the result of cAMP‐independent signal pathways in stimulating hyphal morphogenesis upon GlcNAc induction (Parrino et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…E). Therefore, disruption of cAMP‐PKA signaling did not affect NRG1 transcriptional down‐regulation and GlcNAc‐induced filamentation, a finding which is consistent with the result of cAMP‐independent signal pathways in stimulating hyphal morphogenesis upon GlcNAc induction (Parrino et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…In addition to routine lab condition for hyphal induction which includes the dilution procedure, the yeast-tohypha transition could be also induced in the absence of inoculation. It is found that external stimuli, such as Nacetylglucosamine (GlcNAc), serum or neutral pH, are able to induce hyphal formation efficiently in log phase cells at 378C (Naseem et al, 2011;Su et al, 2016;Parrino et al, 2017). However, it is unknown how hyphal emergence can occur in log phase cells without inoculation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the mci4D and nuo1D mitochondrial mutants grew well in the presence of galactose plus GlcNAc, and could be induced to form hyphae (Figure 3). Although mitochondrial function has been linked to the cAMP pathway and regulation of hyphal growth (Morales et al 2013), it may not be important for GlcNAc to induce hyphae since this amino sugar can activate cAMP-independent pathways (Parrino et al 2017).…”
Section: Ron1 Regulates Glcnac Catabolic Genes and Hyphal Morphogenesismentioning
confidence: 99%
“…Previous studies suggested that the cAMP pathway might be involved in GlcNAc signaling, since a cyr1D mutant that lacks adenylyl cyclase is not induced by GlcNAc to form hyphae. However, a faster-growing pseudorevertant version of the cyr1D strain can be induced to form hyphae, indicating that GlcNAc can induce hyphal morphogenesis by cAMP-independent pathways (Parrino et al 2017).…”
mentioning
confidence: 99%